To teach is to learn twice: The power of a blended peer mentoring approach - Vaughan, Norm; Clampitt, Kayla; Park, Naomi (Teaching and Learning Inquiry, 2016)
Two students at a Canadian university perceived there was a lack of opportunities for peer mentoring support in their teacher education program. They approached a faculty member to co-create and research a blended peer mentoring support program embedded in a first-year education course. This study documents the journey of these two students as co-inquirers in a Scholarship of Teaching and Learning (SoTL) project. Through online surveys and interviews, first-year teacher candidates and faculty involved in the blended peer mentoring program identified four key benefits: new perspectives and expansion of ideas, positive and encouraging reinforcement, supportive connection with second-year students, and probing questions to think more deeply. Conversely, three major challenges were uncovered with the use of digital technologies to support this blended approach to peer mentoring: lack of email notification from the institution’s learning management system (LMS) with regards to the peer mentors’ online contributions, the impersonal nature of online peer mentoring, and the limited number of peer mentors. The major recommendation from this study was to create a blended program assignment to provide all second-year teacher candidates with the opportunity to learn how to serve as peer mentors to students just entering the teacher education program.